The Law of International Governing: Contemporary Priorities - Yu. N. Maleev (Московский журнал международного права)
Discussed in the article are actual theoretical and practical questions of the international governing concept. Shown is the connection of the concept with conflict and crisis situations in different regions and states, the peculiarities of the use of external force in such situations, the role of United Nations Organization and other international organizations in this question.